Assessing the Feasibility of Using Remote Sensing Data and Vegetation Indices in the Estimation of Land Subject to Consolidation - Kocur-Bera, Katarzyna; Małek, Anna (Sensors (Basel, Switzerland), 2024)
The values of vegetation indices can provide a new source of data for use in the estimation of land to be consolidated. The results of research work carried out so far indicate a significant advantage of low-volume imaging over satellite methods when it comes to calculating vegetation index values. This paper analyses multispectral images for the areas of selected croplands acquired via the Sentinel-2 satellite and an unmanned aerial vehicle (UAV) equipped with a multispectral camera. The research work consisted of evaluating NDVI (Normalised Difference Vegetation Index) and SAVI (Soil Adjusted Vegetation Index) values depending on the type of crop grown, the size of the cultivated area and the method of data acquisition. The data obtained were used to assess their potential use in the estimation of land to be consolidated. The effect of land consolidation is primarily to create more favourable living conditions and increase agricultural productivity. The results of the study showed that it would be preferable to use multispectral images acquired using UAVs rather than those from Sentinel satellites. This is due to the insufficient resolution of the satellite data, the correlation of NDVI and SAVI values at only a satisfactory level and the low accuracy of the data obtained for small registered plots of land.